1994
DOI: 10.1021/j100100a028
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Catalysis: Propane Hydrogenolysis Catalyzed by MgO-Supported Tetrairidium

Abstract: A metal carbonyl cluster with a tetrahedral metal frame, [Hk4(CO)11]-, was prepared on the surface of partially hydroxylated MgO powder by adsorption of [Ir4(CO)12]. A supported catalyst was prepared by decarbonylation of the supported [Hzr4(CO)11]-by treatment in He followed by Hz at 300 "C. The surface structures were characterized by inf'rared and X-ray absorption spectroscopies. The decarbonylated cluster had an average Ir-Ir coordination number of 3.4, consistent with the hypothesis that the tetrahedral m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 6 publications
4
23
0
Order By: Relevance
“…Similarly, [Ir4-(CO)12] is synthesized by reductive carbonylation of adsorbed [Ir(C0)2(acac)] on a hydroxylated yA1203 surface. 40 The chemistry of formation of rhodium carbonyl clusters on surfaces is apparently similar to these syntheses of iridium carbonyl clusters and also requires water. The formation of [Rh6(CO) 16] on the surface of alumina has been suggested to be initiated by attack of adsorbed H2O on rhodium subcarbonyls to give mobile, nucleophilic [Rh(CO)&, which was envisaged to react with the rhodium subcarbonyl in a reductive condensation to give the c l u~t e r .~~*~ We suggest that similar chemistry occurred in the formation of the iridium carbonyl cluster in the NaY zeolite45 and also in the formation of [Rb(Co) 16] in NaY This hypothesis about the formation of the rhodium carbonyl cluster is supported by the fact that Rao et al" used C O containing a small amount of water in their synthesis of the cluster from a mononuclear rhodium precursor.…”
Section: Ir-osuppnmentioning
confidence: 78%
“…Similarly, [Ir4-(CO)12] is synthesized by reductive carbonylation of adsorbed [Ir(C0)2(acac)] on a hydroxylated yA1203 surface. 40 The chemistry of formation of rhodium carbonyl clusters on surfaces is apparently similar to these syntheses of iridium carbonyl clusters and also requires water. The formation of [Rh6(CO) 16] on the surface of alumina has been suggested to be initiated by attack of adsorbed H2O on rhodium subcarbonyls to give mobile, nucleophilic [Rh(CO)&, which was envisaged to react with the rhodium subcarbonyl in a reductive condensation to give the c l u~t e r .~~*~ We suggest that similar chemistry occurred in the formation of the iridium carbonyl cluster in the NaY zeolite45 and also in the formation of [Rb(Co) 16] in NaY This hypothesis about the formation of the rhodium carbonyl cluster is supported by the fact that Rao et al" used C O containing a small amount of water in their synthesis of the cluster from a mononuclear rhodium precursor.…”
Section: Ir-osuppnmentioning
confidence: 78%
“…Geometric structures, metal‐support interactions and catalytic activity of the small iridium oxide‐supported clusters were investigated by professor Gates and coworkers. Results of their studies are reported in numerous articles2, 7–12. Almost all of the preparations of nearly uniform supported metal clusters have involved decarbonylation of metal carbonyl clusters, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The most nearly uniform supported metal clusters have been made by decarbonylation of robust metal carbonyl precursors such as [HIr4(CO)11]-and [Ir4(C0)12].4 Tetrairidium clusters have evidently been formed in high yield on MgO by decarbonylation of the anionic precursor, but these were not quite structurally unique; the EXAFS data are represented by a mixture of Ir4 tetrahedra and Ir4 rafts on the MgO surfaces3 Clusters modeled as Ir4 tetrahedra have been formed by decarbonylation of [Ir4(CO)12] on Y-A1203. 4 Our goal was to prepare structurally uniform Ir4 clusters on the surface of MgO. Because the chemistry of the clusters is expected to be affected by the degree of hydroxylation of the MgO surface, we have varied the degree of hydroxylation to find conditions for preparation of structurally uniform clusters.…”
Section: Introductionmentioning
confidence: 99%